REVITALIZATION OF STREET LIGHTING ON THE SELINDUNG BRIDGE OF PANGKALPINANG CITY USES SOLAR ENERGY TO IMPROVE NIGHTTIME AESTHETICS AND SAFETY - aulia, mega; Arya Agustian; Fitriani Rahmawati; Marisa; M.Afdal Samsuddin (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
This study analyzes the opportunities for revitalizing street lighting on the Selindung Bridge, Pangkalpinang City using solar energy. The analysis used several financial analysis methods, including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). This study aims to evaluate the planning of solar-based public street lights in improving aesthetics and nighttime safety. The results of the study indicate that this project is feasible and can be implemented financially based on the parameters evaluated. The budget used in the planning of the solar-powered public street lighting project along the Selindung Bridge road in Pangkalpinang City uses funds from the 2025 Pangkalpinang City Regional Revenue and Expenditure Budget. To consider the safety aspect of road users, it is necessary to plan public street lighting that utilizes solar energy.